2014
DOI: 10.3389/fnbeh.2014.00128
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multiple memory formation on dendritic complexity in the hippocampus and anterior cingulate cortex assessed at recent and remote time points

Abstract: Consolidation processes, involving synaptic and systems level changes, are suggested to stabilize memories once they are formed. At the synaptic level, dendritic structural changes are associated with long-term memory storage. At the systems level, memory storage dynamics between the hippocampus and anterior cingulate cortex (ACC) may be influenced by the number of sequentially encoded memories. The present experiment utilized Golgi-Cox staining and neuron reconstruction to examine recent and remote structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…For instance, dendritic spine growth in the ACC for context memories requires weeks to complete (Restivo et al 2009;Vetere et al 2011), which is consistent with long-term systems consolidation views. However, a more recent study showed no differences in dendritic spine complexity in the ACC between recent and remote memories (Wartman and Holahan 2014). Regardless of these discrepant findings, the current evidence supports the cognitive processing hypothesis of Rudy et al and suggests that future studies involving remote memory and the ACC should take into account cognitive demand when interpreting ACC activation during memory retrieval.…”
supporting
confidence: 64%
“…For instance, dendritic spine growth in the ACC for context memories requires weeks to complete (Restivo et al 2009;Vetere et al 2011), which is consistent with long-term systems consolidation views. However, a more recent study showed no differences in dendritic spine complexity in the ACC between recent and remote memories (Wartman and Holahan 2014). Regardless of these discrepant findings, the current evidence supports the cognitive processing hypothesis of Rudy et al and suggests that future studies involving remote memory and the ACC should take into account cognitive demand when interpreting ACC activation during memory retrieval.…”
supporting
confidence: 64%
“…), indicating that a higher demand of information processing leads to an accelerated ACC‐dependency of CFC memory. This idea is supported by two recent articles (Wartman and Holahan, ), showing that multiple learning experiences induce changes in dendritic spine complexity and c‐fos expression in ACC at short delays that resemble those of remote memories. In addition, the HPC plays a crucial role in neocortical memory‐related plasticity (Sutherland et al, ), suggesting that the accelerated HPC‐to‐ACC memory reorganization is actively induced by the HPC.…”
Section: Discussionmentioning
confidence: 66%
“…The RAM is a complex memory paradigm comprising many components as working memory, spatial memory and long-term memory. Involvement of the hippocampus in working memory has been reported [ 23 ], however, increased dendritic complexity following working memory in the hippocampus is reported in CA1 where only spine count was analyzed showing increased spine density following consolidation of working memory [ 24 ].…”
Section: Discussionmentioning
confidence: 99%